THE ROLE OF INTERLEUKIN-6 GENE IN DEVELOPMENT OF IDIOPATHIC SICK SINUS SYNDROME - S. Yu. Nikulina; O. V. Marilovtseva; A. A. Chernova; S. S. Tretyakova; D. A. Nikulin; V. N. Maksimov (Российский кардиологический журнал)
Aim. To study the association of polymorphisms rs1800795 of gene IL-6 with the development of sick sinus node syndrome (SSS).Material and methods. Totally, 109 patients studied, with idiopathic SSS, and 59 of their healthy relatives of I, II, III grade of relation, and 173 controls. Patients from main group were selected to subgroups according to sex and clinical type of the disease. All patients underwent standard clinical and instrumental cardiological assessment and molecular-genetic test of DNA. Statistics was done with software “Statistica 7.0”.Results. There was significant predominance of homozygous genotype of rare allele of the studied gene in controls (18,5%±3,0) comparing to idiopathic SSS patients (8,5%±3,1), p=0,039, and to subgroup of males with SSS (5,2%±8 among SSS males versus 30,8%±9,1 among controls, р=0,03). Also there was significant predominance of the widespread genotype IL-6 among males with compensated SSS variant (69,2%±12,8) comparing to the controls (23,1%±8,3, р=0,005).Conclusion. Probably the homozygous genotype GG of gene IL-6 is protective against idiopathic SSS.